2020
DOI: 10.1017/jfm.2020.621
|View full text |Cite
|
Sign up to set email alerts
|

Law of the wall for a temporally evolving vertical natural convection boundary layer

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(70 citation statements)
references
References 42 publications
8
61
1
Order By: Relevance
“…The present study follows our previous work in Ke et al (2020), where the near-wall dynamics of the temporally developing turbulent NCBL adjacent to a vertical isothermal wall was investigated. In the present study, we investigate the bulk mean flow (later identified as the plume-like region in § 3) of the turbulent NCBL in terms of the integral model framework outlined by .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The present study follows our previous work in Ke et al (2020), where the near-wall dynamics of the temporally developing turbulent NCBL adjacent to a vertical isothermal wall was investigated. In the present study, we investigate the bulk mean flow (later identified as the plume-like region in § 3) of the turbulent NCBL in terms of the integral model framework outlined by .…”
Section: Introductionmentioning
confidence: 94%
“…Grossmann & Lohse 2000, 2001 where a bulk-dominated ultimate turbulent regime is thought to be achieved at very high Grashof numbers. Our previous work on the temporally developing NCBL in Ke et al (2020) also investigated the law of the wall in the near-wall region for the NCBL using DNS. That study showed that the mean temperature profile for the turbulent NCBL appears self-similar and follows a log-law; whereas such a log-law is modified for the mean streamwise velocity profile due to the additional buoyancy in the near-wall region, and that the near-wall buoyancy becomes increasingly weak such that the NCBL would be asymptotic to momentum-dominated behaviour in the limit of higher Grashof number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical solver has been validated by a number of natural convection studies and the grid resolution is found sufficient for DNS [4,15]. The DNS data used in the present study has also been previously reported in [5].…”
Section: Methodsmentioning
confidence: 91%
“…To initiate laminar-turbulent transition, stream-wise and spanwise perturbations, given by equation (5), are augmented to the laminar temperature solution (4).…”
Section: Methodsmentioning
confidence: 99%